2023
DOI: 10.1021/acs.inorgchem.3c01172
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bis(imino)acenaphthene (Bian)-Derived Ligands on the Cytotoxicity, DNA Interactions, and Redox Activity of Palladium(II) Bipyridine Complexes

Veronika I. Komlyagina,
Nikolai F. Romashev,
Victoria K. Besprozvannykh
et al.

Abstract: A series of heteroleptic bipyridine Pd­(II) complexes based on 1,2-bis­[(2,6-diisopropylphenyl)­imino]­acenaphthene (dpp-Bian) or 1,2-bis­[(2,4,6-trimethylphenyl)­imino]­acenaphthene (tmp-Bian) were prepared. All complexes were fully characterized by spectrochemical methods, and their crystal structures were confirmed by X-ray diffraction analysis. The 72 h stability of heteroleptic bipyridine Pd­(II) complexes with Bian ligands under physiological conditions was investigated using 1H NMR spectroscopy. The ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Previously it was reported that uncoordinated BIAN ligands, including dpp-bian, did not display biological activity due to poor solubility in biological media. 20,21 Herein, we also observed that dpp-bian and dpp-mian ligand were not characterized by any cytotoxicity in all tested cell lines. However, substitution of bulky dpp fragments with methyl groups in 2-Me-Ph-bian or 4-Me-Ph-bian resulted in the considerable improvement of their solubility in DMSO and, as a consequence, the increase of their cytotoxicity.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Previously it was reported that uncoordinated BIAN ligands, including dpp-bian, did not display biological activity due to poor solubility in biological media. 20,21 Herein, we also observed that dpp-bian and dpp-mian ligand were not characterized by any cytotoxicity in all tested cell lines. However, substitution of bulky dpp fragments with methyl groups in 2-Me-Ph-bian or 4-Me-Ph-bian resulted in the considerable improvement of their solubility in DMSO and, as a consequence, the increase of their cytotoxicity.…”
Section: Resultsmentioning
confidence: 60%
“…We developed a series of heteroleptic complexes of palladium and platinum with dpp-bian and tmp-bian ligands, which demonstrated anticancer activity in the range of low micromolar concentrations. 20,21 It should be noted that the distribution of studies on metal complexes with BIAN ligands is extremely uneven. While there are many studies on the complexes of main group elements and 3d metals, the data available for BIAN complexes of 4d and especially 5d metals are limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 The Pd-N bond lengths are 2.01-2.10 Å, which is in the standard range of values for palladium diimine complexes. 30,31,56 Crystal packings of 3 and 4 are similar (Fig. S15, ESI †).…”
Section: X-ray Structure Descriptionmentioning
confidence: 90%
“…For cations of 3-5, HOMOs are almost completely localized on the acenaphthenehydrazone fragment, while LUMOs are localized on Ar-bian, which is typical for square planar Pd/Ar-bian complexes. 30,31 The composition of frontier orbitals is presented in Table S2 (ESI †).…”
Section: Redox Propertiesmentioning
confidence: 99%